3D navigation system for virtual reality based on 3D game engine - K. H., Sharkawi; Ujang, Muhamad Uznir; Abdul Rahman, Alias (2008)
Intense competitions in computer related industries have lead to the development of new amazing technologies. This drastically improved 3D game engine, which was initially developed for computer games, to become more adaptable and versatile thus enables it to be incorporated with GIS applications for them to support 3D capabilities.3D navigation is one of the 3D GIS components that benefited from this technology.Visualizing geospatial data in 3D environment is more relevant for navigation systems rather than using symbolic 2D maps because 3D visualization can provides users with the real spatial information (colors and shapes) and the 3D models resembles the real world objects. Navigational landmarks and other features that can be very helpful when navigating in the real world are easily spotted in the 3D environment but hardly available in 2D maps. By incorporating a database, users can even carry out some spatial analyses that greatly improve the system’s reliability. This paper describes the development of 3D navigation system in virtual 3D (indoor and outdoor) environment by utilizing a freely available 3D game engine couple with GIS elements.